Political Economy of Fiscal Reforms in the 1990s (The Pakistan Development Review, 2001)
Throughout the decade of the 1990s, major emphasis in Pakistan remained on fiscal reform as a part of the reform programmes undertaken by the various governments of Pakistan. Fiscal reform assumes significance considering the high budget deficits that Pakistan has been experiencing. These have added to Pakistan’s total debt burden in general and external debt in particular. Increase in the burden of debt adds to debt-servicing expenditure which further feeds back into the issue of high fiscal deficit. Debt-servicing increased to almost 47 percent1 by the middle of the decade of 1990s and comprised 8.3 percent of the GDP, up from less than 1 percent mid-1960s. Pakistan’s external debt at over $32 billion2 in 1998 was 41 percent of its GNP which was amongst the highest in the South Asian region with India’s at 20 percent of GNP in the same year and Sri Lanka’s also at 41 percent3 of its GNP. In this paper, we attempt to explore the rationale behind the emphases on the improvement in both the deficit-to-GDP and the tax-to-GDP ratios that have remained the cornerstones of Pakistan’s fiscal reform effort in the decade of the 1990s. Section 2 is a discussion of the extent of successes and failures of the fiscal reform effort thus far and explores the relationship between tax generation and budget deficit. Section 3 discusses the impact of expenditures on budget deficit. Section 4 shows the rise in dependence on external sources of financing. Section 5 gives the conclusions.